1991
DOI: 10.1056/nejm199105303242204
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Controlled Trial of Ursodiol for the Treatment of Primary Biliary Cirrhosis

Abstract: Ursodiol is a safe and effective treatment for primary biliary cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
364
2
12

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 702 publications
(388 citation statements)
references
References 34 publications
10
364
2
12
Order By: Relevance
“…UDCA has been shown to improve liver function tests, liver histology, and survival in primary biliary cirrhosis, [1][2][3][4][5][6] and similar effects have been observed in other cholestatic diseases. [7][8][9][10][11][12][23][24][25] The mechanism of action of UDCA in hepatobiliary diseases is still not completely understood.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…UDCA has been shown to improve liver function tests, liver histology, and survival in primary biliary cirrhosis, [1][2][3][4][5][6] and similar effects have been observed in other cholestatic diseases. [7][8][9][10][11][12][23][24][25] The mechanism of action of UDCA in hepatobiliary diseases is still not completely understood.…”
Section: Discussionmentioning
confidence: 94%
“…In primary biliary cirrhosis, UDCA treatment slows progression of the disease and improves survival. [1][2][3][4][5][6] In primary sclerosing cholangitis (PSC), UDCA improves laboratory parameters, [7][8][9][10][11][12] and its effect on the outcome is currently being evaluated. There is evidence 11,12 that high doses (Ն20 mg/kg/d) of UDCA may be more effective than average doses (15 mg/kg/d).…”
mentioning
confidence: 99%
“…19,21,30 Although the mechanism(s) of the UDCA effect on the improvement of liver function are still unclear, it has been postulated that UDCA, a less hydrophobic bile acid, displaces the more hydrophobic, potentially toxic bile acids from the membranes, protecting the hepatocytes. 31 Conversely, the immunomodulatory properties [32][33][34] as well as an antiapoptotic effect of UDCA 18 have been indicated.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Furthermore, recent reports have indicated a variety of characteristics of UDCA in immunomodulation 17 and anti-apoptosis. 18 Despite its long history as a safe drug for patients with various hepatobiliary disorders, such as primary biliary cirrhosis 19,20 and chronic viral hepatitis, 21 the mechanism of action of UDCA has not been fully understood. In addition, although the improvement of biochemical data in patients with these chronic hepatic diseases has been reported, the benefit of its administration for patients in advanced stage has not been determined.…”
mentioning
confidence: 99%
“…[1][2][3][4] In addition, a combined analysis, pooling 548 patients involved in three large trials using a similar dose of UDCA, has demonstrated that 4-year UDCA therapy increases survival free of orthotopic liver transplantation (OLT). 5 In untreated patients with PBC, elevated levels of serum bilirubin level (SBL) have been consistently found to be an independent predictor of a poor prognosis.…”
mentioning
confidence: 99%